Post-COVID-19 complications in home and hospital-based care: A study from Dhaka city, Bangladesh - Khandker, Salamat; Akther, Aivee; Syed, Billal H.; Shafiullah, Rezoun; Ahmed, Kawsar; Chowdhury, Alauddin A.; Khan, Salim (Frontiers in Rehabilitation Sciences, 2022)
A cross-sectional survey was undertaken to understand the management and post-COVID-19 complications among hospital and home-treated participants. Retrospective information was collected from four COVID-19 hospitals and four community settings. Using probability proportional sampling, 925 participants were selected. Data were collected using a semi-structured questionnaire. Bivariate and multivariate logistic regression analysis and the exact chi-square test was utilized to analyze the association. A total of 659 participants responded; 375 from hospitals and 284 from communities. Above 75% were treated at home, and 65% of the hospital-treated participants were referred after home treatment. Participants treated at home-to-hospital and directly in the hospital had 1.64 and 3.38 times longer recovery times respectively. A significant increasing trend of co-morbidities was found among referred and hospital-treated participants. Age, education, physical exercise, preventive measures, sunlight exposure, balanced food intake, and junk food avoidance were significantly associated with the place of treatment. Post-COVID-19 difficulties of all factors were significant for home treatment participants, whilst depression, chest pain, and digestive disorders were significant for hospital-treated participants. There are statistically significant differences in post-COVID-19 complications between home-and hospital-treated participants.